Home-Based Work and Home-Based Workers (1800-2021) - Nilsson, Malin (Studies in Global Social History, 2022)
Home-Based Work and Home-Based Workers (1800-2021) is about the past and present of home-based work and homebased workers between 1800 and 2021 from a global perspective.; Readership: All interested in social and economic history, and especially in the past and present of home-based work and homebased workers.